Gerakan Dakwah Jemaah Tabligh terhadap Muslim Dikalangan Penduduk Mayoritas Non Muslim di Kecamatan Siantar Marihat Kota Pematang Siantar - Dimas Alwi, Muhammad; Jailani, Muhammad; Susanti, Neila (Comit: Communication, Information and Technology Journal, 2024)
This research aims to collect information about the Tablighi Jamaah's da'wah movement among the non-Muslim majority in Siantar Marihat District, Pematang Siantar city. In this research, the author will observe religious activities carried out by members of the Tablighi Jamaah who come to Siantar Marihat District. It is hoped that this religious activity can provide a special experience in preaching among the non-Muslim majority. This research is included in the field research category with a qualitative approach. The data collection technique used in this research is triangulation, including observation, interviews and documentation. Data analysis was carried out using data reduction, data presentation and verification techniques. The data sources in this research involved the administrators of the Al-hidayah mosque, the emir of the tabligh congregation, and the community as research informants. Based on the results of the research conducted, it appears that the Muslim community has two perceptions regarding the Tablighi Jama'ah in viewing their arrival in Siantar Marihat District, Pematang Siantar City. First, the majority of the Muslim community considers that the religious activities often carried out by the Tablighi Jama'ah provide positive religious values ​​for the residents of Siantar Marihat sub-district. Through these activities, the Tablighi Jamaah can strengthen ties between residents and other communities. Activities that are often carried out include recitation of the Koran, halaqo/liqo, ikhtikaf at the mosque, and socializing with the community while preaching. Meanwhile, the second perception is that there is still limited knowledge about the Tablighi Jama'ah which causes some people to have a negative view of them.